Illicit drug use in university students in the UK and Ireland: a PRISMA-guided scoping review - Maeve Boden; Ed Day (BMC, 2023)
Abstract Background Interest in the health and well-being of university students has increased in the UK and Ireland in the past two decades as their numbers have grown. Recent high-profile deaths of students after using illicit drugs have highlighted the importance of the topic for policy makers. This scoping review maps the state of the existing literature evaluating use of illicit drugs in university students in the UK and Ireland. It aims to highlight research gaps and inform policy. Method We conducted a systematic search of papers related to psychoactive drug use in university students in the UK and Ireland published before August 2021. The 18 extracted study characteristics included author(s); year of publication; journal; location of data collection; study design; delivery method (e.g., online survey, in-person, postal survey); number of participants; response rate; participant course of study, year of study, degree level (i.e., undergraduate, postgraduate), gender and age; time-period assessed (e.g., lifetime, current use, past 12 months); primary aim; primary outcome; ethical approval; and funding source. Results The PRISMA-guided search strategy identified 1583 papers for abstract review; of 110 papers retained for full-text review, 54 studies met criteria for inclusion for this paper. Primary outcomes were coded into five groups: prevalence and patterns of drug use; factors associated with drug use; attitudes and knowledge about, and motivation for, drug use; supply of drugs; consequences of drug use. The results show that there is no coherent body of research in this area. The prevalence of reported drug use has crept up and the range of substances reported has broadened over time, and attitudes to drugs on average have normalised. However, there are significant methodological limitations that limit the utility of these findings. There was little evidence of published work on prevention of, or intervention to reduce, drug-related harms. Conclusion The domains identified offer a framework for university administrators, researchers and policy makers to understand the potential response to drug use in university students in the UK and Ireland. Recommendations are made to fill the gaps in the research evidence base.